Key Factors of Technology Transfer in The Moroccan Aerospace Sector: An Analysis Using Design of Experiments and SERVQUAL - Bennani, Fatima Zahra; Dakkak, Badr (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The development of Morocco's aerospace sector largely depends on its ability to attract foreign companies and promote technology transfer to local actors. In this context, identifying the key factors driving this dynamic is a strategic challenge to strengthen the country's competitiveness within the global value chain. This paper addresses this issue by applying a rigorous methodology to highlight the most relevant levers for supporting the process. In fact, the Design of Experiments (DOE) methodology, well-recognized for its effectiveness across various fields, was adopted. The study was conducted in collaboration with three categories of stakeholders: Moroccan aerospace professionals, relevant government officials, and academic researchers. Together, they established a list of potential factors derived from an extensive literature review. Data evaluation relied on the SERVQUAL method, applied to three distinct responses corresponding to the three stakeholder groups. This approach allowed for more precise and reliable analysis and comparison of results. The findings provide a valuable decision-making tool for stakeholders and policymakers, enabling them to target the most influential levers to reinforce technology transfer in the Moroccan aerospace sector.